Ruthenibacterium lactatiformans gen. nov., sp. nov., an anaerobic, lactate-producing member of the family Ruminococcaceae isolated from human faeces - Shkoporov, Andrei N.; Chaplin, Andrei V.; Shcherbakova, Victoria A.; Suzina, Natalia E.; Kafarskaia, Lyudmila I.; Bozhenko, Vladimir K.; Efimov, Boris A. (International journal of systematic and evolutionary microbiology, 2016)
Two novel strains of Gram-stain-negative, rod-shaped, obligately anaerobic, non-spore-forming, non-motile bacteria were isolated from the faeces of healthy human subjects. The strains, designated as 585-1T and 668, were characterized by mesophilic fermentative metabolism, production of d-lactic acid, succinic acid and acetic acid as end products of d-glucose fermentation, prevalence of C18 : 1ω9, C18 : 1ω9 aldehyde, C16 : 0 and C16 : 1ω7c fatty acids, presence of glycine, glutamic acid, lysine, alanine and aspartic acid in the petidoglycan peptide moiety and lack of respiratory quinones. Whole genome sequencing revealed the DNA G+C content was 56.4-56.6 mol%. The complete 16S rRNA gene sequences of the two strains shared 91.7/91.6 % similarity with Anaerofilum pentosovorans FaeT, 91.3/91.2 % with Gemmiger formicilis ATCC 27749T and 88.9/88.8 % with Faecalibacterium prausnitzii ATCC 27768T. On the basis of chemotaxonomic and genomic properties it was concluded that the strains represent a novel species in a new genus within the family Ruminococcaceae, for which the name Ruthenibacterium lactatiformans gen. nov., sp. nov. is proposed. The type strain of Ruthenibacterium lactatiformans is 585-1T (=DSM 100348T=VKM B-2901T).